Thromboelastography in mild, chronic liver disease: challenging conventional coagulation tests preceding liver biopsy. (3rd September 2018) - Veronese, LR; Miller, M; Spearman, WC
Abstract : Patients presenting for liver biopsy may have a deficiency of the synthetic function of the liver. They commonly undergo testing of their INR, which is used to decide if there may be a bleeding risk and if that needs to be mitigated by the administration of clotting factors. This study aimed to observe the coagulation profile of these patients via a thromboelastogram (TEG), and to search for a relationship between the traditionally used INR and the R-time of the TEG. A prospective observational pilot study was conducted over a seven-month period. An FBC, INR and kaolin activated thromboelastogram were performed on each patient. Spearman's correlation coefficient was used to determine the relationship between the INR and the R-time of the TEG. The TEG was performed on 28 participants. Two were excluded from analysis as they had received Vitamin K. Twenty-three patients (88%) had abnormal liver function tests. Drug or toxins were responsible for liver injury in 15 (58%) participants. Twenty-two (85%) had normal platelet counts. Three (12%) were found to be hypocoagulable, four (15%) were hypercoagulable, and the remaining 19 (73%) had normal thromboelastography. The three (12%) participants who were hypocoagulable had a normal platelet count. No association was found between INR and the R-time of TEG (Spearman's rho −0.20, p  = 0.34). In the two participants (8%) with a raised INR (1.26 and 1.7 respectively), the TEG suggested a normal or hypercoagulable status. This study revealed that most patients with mild, chronic liver disease presenting for liver biopsy have a normal TEG. There was no association between INR and the R-time of the TEG. This suggests that INR may not be a reliable test of coagulation status in these patients with mild chronic liver disease, which is contrary to the traditional practice of using INR to infer coagulation status. Further larger studies looking specifically at patients with drug and toxin induced liver injury are warranted.